Respuestas

  • Usuario de Brainly
2013-05-19T16:53:34+02:00
1)   4+(21+∛24:3 - (7¹ - √ 25)² )+(18-6) .12 -(2+(8+8).6)=
     4 + (21 +
∛8 - (7 - 5)²) + (12) . 12 - (2 + (16).6) =
     4 + (21 + 2 - (2)²) + 144 - (2 + 96) =
     4 + (21 + 2 - 4) + 144 - (98) =
     4 + 19 + 144 - 98 =
          69

2)
13.4+(1500-26.(8+7) -108) - (4+(√25+5).7+18)=
       52 + (1500 - 26. 15 - 108) - (4 +( 5+ 5) .7 + 18) =
        52 + (1500 -  390 - 108 ) - (4 + (10) .7 + 18) =
       52 +  1002 - ( 4 + 70 + 18) =
       52 + 1002 - 92 =
          962
3)  (20.30:5+660:(∛64+2³) )+3800:25+(150+(10+9).3+48)=
   
(20. 6+660:(4+ 8) )+3800:25+(150+(19).3+48)=
     (120+660:(12) ) + 152 + (150+ 57 + 48)=
      (120+ 55 ) + 152 + (150+ 57 + 48)=
      175 + 152 + 255 =
     582

espero que te sirva, salu2!!!!!